Bioinformatics of 1-aminocyclopropane-1-carboxylic acid synthase gene from eggplant and its expression analysis in response to adversity stresses - WAN Faxiang; WANG Lianzhen; GAO Jun (浙江大学学报. 农业与生命科学版, 2021)
Based on the early transcriptome data of eggplant under cold stress, the 1-aminocyclopropane-1-carboxylic acid (ACC) synthase gene SmACS was selected out. It was found that the encoded amino acid sequence of SmACS had the highest homology with soybean ACS protein, and included seven conserved domains unique to ACC synthase and 11 invariant amino acid residues. The SmACS gene was located on the chromosome 8, and the full length of this gene was 3 550 bp, whose length of coding sequence (CDS) region was 1 437 bp. It contained three introns and four exons, which belonged to a typical ACS gene structure. The SmACS protein consisted of 478 amino acids, with a molecular mass of 54.03 kDa, isoelectric point of 6.48 and hydrophilic index of －0.206. It was an unstable non-secreted hydrophilic protein located in the cytoplasm. The main components of SmACS protein were α-helix and random coils. It had a conserved Aminotran_1_2 domain and contained 39 phosphorylation sites, of which serine and threonine were the main ones. The SmACS protein mainly interacted with ACC oxidase. The promoter of SmACS gene contained Cis-acting elements related to abscisic acid, ethylene, cold stress, salicylic acid and wound responses. The results of real-time fluorescent quantitative polymerase chain reaction (qRT-PCR) confirmed that the expression of SmACS gene was induced by cold, heat, drought and salt stresses, among which cold stress was the most significant. The above results lay theoretical basis for functional identification of SmACS gene from eggplant.